Canine and Phocine Distemper Viruses: Global Spread and Genetic Basis of Jumping Species Barriers - Judith Kennedy; J.A. Earle; Shadia Omar; Hani’ah Abdullah; Ole Nielsen; Melody Roelke-Parker; S. Cosby (Viruses, 2019)
Canine distemper virus (CDV) and phocine distemper (PDV) are closely-related members of the Paramyxoviridae family, genus morbillivirus, in the order Mononegavirales. CDV has a broad host range among carnivores. PDV is thought to be derived from CDV through contact between terrestrial carnivores and seals. PDV has caused extensive mortality in Atlantic seals and other marine mammals, and more recently has spread to the North Pacific Ocean. CDV also infects marine carnivores, and there is evidence of morbillivirus infection of seals and other species in Antarctica. Recently, CDV has spread to felines and other wildlife species in the Serengeti and South Africa. Some CDV vaccines may also have caused wildlife disease. Changes in the virus haemagglutinin (H) protein, particularly the signaling lymphocyte activation molecule (SLAM) receptor binding site, correlate with adaptation to non-canine hosts. Differences in the phosphoprotein (P) gene sequences between disease and non-disease causing CDV strains may relate to pathogenicity in domestic dogs and wildlife. Of most concern are reports of CDV infection and disease in non-human primates raising the possibility of zoonosis. In this article we review the global occurrence of CDV and PDV, and present both historical and genetic information relating to these viruses crossing species barriers.